3D NIR‐II Molecular Imaging Distinguishes Targeted Organs with High‐Performance NIR‐II Bioconjugates. Issue 13 (15th February 2018) - Zhu, Shoujun; Herraiz, Sonia; Yue, Jingying; Zhang, Mingxi; Wan, Hao; Yang, Qinglai; Ma, Zhuoran; Wang, Yan; He, Jiahuan; Antaris, Alexander L.; Zhong, Yeteng; Diao, Shuo; et al.
Abstract: Greatly reduced scattering in the second near‐infrared (NIR‐II) region (1000–1700 nm) opens up many new exciting avenues of bioimaging research, yet NIR‐II fluorescence imaging is mostly implemented by using nontargeted fluorophores or wide‐field imaging setups, limiting the signal‐to‐background ratio and imaging penetration depth due to poor specific binding and out‐of‐focus signals. A newly developed high‐performance NIR‐II bioconjugate enables targeted imaging of a specific organ in the living body with high quality. Combined with a home‐built NIR‐II confocal set‐up, the enhanced imaging technique allows 900 µm‐deep 3D organ imaging without tissue clearing techniques. Bioconjugation of two hormones to nonoverlapping NIR‐II fluorophores facilitates two‐color imaging of different receptors, demonstrating unprecedented multicolor live molecular imaging across the NIR‐II window. This deep tissue imaging of specific receptors in live animals allows development of noninvasive molecular imaging of multifarious models of normal and neoplastic organs in vivo, beyond the traditional visible to NIR‐I range. The developed NIR‐II fluorescence microscopy will become a powerful imaging technique for deep tissue imaging without any physical sectioning or clearing treatment of the tissue. Abstract : Two‐color live molecular imaging across the second near‐infrared (NIR‐II) window (1000–1700 nm) is achieved by high‐performance NIR‐II bioconjugates. A great 900 µm scanning depth is achieved by NIR‐II one‐photon confocal 3D molecular imaging and provides a new solution for simultaneously visualizing tissue structure and allowing molecular phenotyping in a large tissue volume.